Mechanical Communication at the Immunological Synapse. Issue 4 (April 2017) - Basu, Roshni; Huse, Morgan
Abstract : T and B lymphocytes communicate by forming immunological synapses with antigen-presenting target cells. These highly dynamic contacts are characterized by continuous cytoskeletal remodeling events, which not only structure the interface but also exert a considerable amount of mechanical force. In recent years, it has become increasingly clear that synaptic forces influence information transfer both into and out of the lymphocyte. Here, we review our current understanding of synapse mechanics, focusing on its role as an avenue for intercellular communication. Trends: Dynamic cell–cell interfaces mediate a large fraction of intercellular communication in the immune system. It is becoming increasingly clear that mechanical forces are critical for the proper function of these interactions. The T cell IS generates forces that mechanically activate ligand-bound integrins and antigen receptors, which behave like 'catch bonds'. For antigen receptors, binding under physical load enables better discrimination between strong and weak ligands. T cells also exert force across the IS. Recent work indicates that this force can potentiate the activity of secreted proteins, which implies that lymphocytes combine physical and chemical output to enhance the efficiency of intercellular communication.